2022
DOI: 10.1007/s11010-022-04526-w
|View full text |Cite
|
Sign up to set email alerts
|

PI3K(p110α) as a determinant and gene therapy for atrial enlargement in atrial fibrillation

Abstract: Atrial fibrillation (AF) is an irregular heart rhythm, characterised by chaotic atrial activation, which is promoted by remodelling. Once initiated, AF can also propagate the progression of itself in the so-called ‘‘AF begets AF’’. Several lines of investigation have shown that signalling molecules, including reactive oxygen species, angiotensin II, and phosphoinositide 3-kinases (PI3Ks), in presence or absence of cardiovascular disease risk factors, stabilise and promote AF maintenance. In particular, reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 98 publications
0
0
0
Order By: Relevance
“…In non-obese patients, LA enlargement is possibly merely a consequence of prolonged hemodynamic stress due to heterogeneous conditions with LA pressure or volume overload, that can be also aggravated by atrial stand-still during AF episodes. On the other hand, genetic factors promoting LA enlargement and AF have also been identified (36,37). However, LA enlargement in obese patients seems to carry a higher propensity for AF compared to non-obese patients, which highlights the additional proarrhythmogenic impact of local and systemic inflammatory condition mediated by obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In non-obese patients, LA enlargement is possibly merely a consequence of prolonged hemodynamic stress due to heterogeneous conditions with LA pressure or volume overload, that can be also aggravated by atrial stand-still during AF episodes. On the other hand, genetic factors promoting LA enlargement and AF have also been identified (36,37). However, LA enlargement in obese patients seems to carry a higher propensity for AF compared to non-obese patients, which highlights the additional proarrhythmogenic impact of local and systemic inflammatory condition mediated by obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that spontaneous arrhythmogenic "calcium waves" can result from genetic mutations of RyR2 but are more often due to an increase in the time of its open state [61][62][63][64][65]. Defects in its modular coupling with regulatory proteins of the cytosol, such as CaM, Epacl, PDE, FKBP12.6, PKA, PP1, calstabin, etc., or with Ca 2+ -binding proteins localized in the lumen of the SR (junctin, triadin, and calsequestrin), form temporary macromolecular complexes and can lead to a disruption of the RyR2 gate function [62,[66][67][68][69].…”
Section: Cardiac Ryanodine Receptor (Ryr2)mentioning
confidence: 99%
“…Ragab et al reported an increased risk of developing AF in individuals with a parental history of AF 8 . In addition, based on molecular studies, it was found that the abnormal expression of PI3Ks , SLC7A11 , CXCL12 , and other genes participated in the pathogenesis of AF 9–11 . Therefore, understanding the regulatory genes of AF can aid in early identification of individuals at high risk for developing AF.…”
Section: Introductionmentioning
confidence: 99%
“… 8 In addition, based on molecular studies, it was found that the abnormal expression of PI3Ks , SLC7A11 , CXCL12 , and other genes participated in the pathogenesis of AF. 9 , 10 , 11 Therefore, understanding the regulatory genes of AF can aid in early identification of individuals at high risk for developing AF. HF is a cardiovascular disease characterized by symptoms such as fatigue, significantly reduced exercise endurance, oedema, and paroxysmal nocturnal dyspnoea.…”
Section: Introductionmentioning
confidence: 99%